Random walks in the quarter plane : algebraic methods, boundary value problems, applications to queueing systems and analytic combinatorics /: algebraic methods, boundary value problems, applications to queueing systems and analytic combinatorics. (2017) - Fayolle, G (Guy), 1943-; Iasnogorodski, Roudolf, 1938-; Malyshev, V. A (Vadim Aleksandrovich)
No abstract available